Confocal microscopy of plasmonic hybrid nanostructures - Bujak, Lukasz; Krajnik, Bartosz; Olejnik, Maria; Czechowski, Nikodem; Piatkowski, Dawid; Mackowski, Sebastian (Photonics Letters of Poland, 2012)
We describe the results of confocal microscopy imaging of a hybrid nanostructure composed of elongated gold nanoparticles and light-harvesting complexes LH2 from purple bacteria. The images obtained for the hybrid nanostructure feature strong inhomogeneity of fluorescence intensity as well as its higher average value in comparison with the reference. Both are the result of plasmon excitations generated in metallic nanoparticles. We observe that excitation into longitudinal plasmon resonance of the nanorods (808nm) yields larger fluorescence enhancement than for excitation of the transverse mode (556nm). Full Text: PDF References: S. Maier, Plasmonics: Fundamentals and Applications (New York, Springer Science + Business Media LLC 2007). Anger, P. Bharadwaj, L. Novotny, "Enhancement and Quenching of Single-Molecule Fluorescence",Phys. Rev. Lett. 96, 113002 (2006).CrossRef K. Ray, R. Badugu, J.R. Lakowicz, "Metal-Enhanced Fluorescence from CdTe Nanocrystals: A Single-Molecule Fluorescence Study", J. Am. Chem. Soc. 128, 8998 (2006).CrossRef Ł. Bujak, N. Czechowski, D. Piatkowski, R. Litvin, S. Mackowski, T.H.P. Brotosudarmo, R.J. Cogdell, S. Pichler, W. Heiss, , " Fluorescence enhancement of light-harvesting complex 2 from purple bacteria coupled to spherical gold nanoparticles", Appl. Phys. Lett. 99, 173701 (2011).CrossRef J.B. Nieder, R. Bittl, M. Brecht, "Fluorescence Studies into the Effect of Plasmonic Interactions on Protein Function", Angew. Chem. Int. Ed. 49, 10217 (2010).CrossRef A.O. Govorov, I. Carmeli,"Hybrid Structures Composed of Photosynthetic System and Metal Nanoparticles: Plasmon Enhancement Effect", Nano Letters 7, 620 (2007).CrossRef G. McDermott, S. Prince, A. Freer, A. Hawthornthwaite-Lawless, M. Papiz, R.J. Cogdell, N. Isaacs, "Crystal structure of an integral membrane light-harvesting complex from photosynthetic bacteria", Nature 374, 517 (1994).CrossRef G.W. Bryant, F.J. Garcia de Abajo, J. Aizpurua, "Mapping the Plasmon Resonances of Metallic Nanoantennas", Nano Letters 8, 631 (2008).CrossRef C.J. Murphy, N.R. Jana, "Controlling the Aspect Ratio of Inorganic Nanorods and Nanowires", Adv. Mater. 14, 80 (2002).CrossRef B. Krajnik,T. Schulte, D. Piątkowski, N. Czechowski, E. Hofmann, S. Mackowski,"SIL-based confocal fluorescence microscope for investigating individual nanostructures", Cent. Eur. J. Phys. 2, 293 (2011).CrossRef